Answer:
2.66
Step-by-step explanation:
6 is your answer, hope it helped
1/a
The b^-3 in the denominator and numerator cancel out
First, you would get the decimal form of 67% by moving the decimal (At the end of most whole numbers.) over two, giving you .67.
Next, multiply 296 by this new decimal- .67*296=198.32.
There you go! : )
Answer:
y = 6/7
Step-by-step explanation:
The equation given is:
-3 = 7(y - 9/7)
To solve this, we will expand the bracket and afterwards, collect like terms:
-3 = (7*y) - (9/7 * 7)
-3 = 7y - 9
Collecting numeric terms to the left hand side:
-3 + 9 = 7y
=> 6 = 7y
=> y = 6/7
That is the solution.